2016
DOI: 10.1016/j.cub.2015.12.065
|View full text |Cite
|
Sign up to set email alerts
|

Effective Modulation of Male Aggression through Lateral Septum to Medial Hypothalamus Projection

Abstract: Summary Aggression is a prevalent behavior in the animal kingdom that is used to settle competition for limited resources. Given the high risk associated with fighting, the central nervous system has evolved an active mechanism to modulate its expression. Lesioning the lateral septum (LS) is known to cause “septal rage”, a phenotype characterized by a dramatic increase in the frequency of attacks. To understand the circuit mechanism of the LS-mediated modulation of aggression, we examined the influence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
156
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(173 citation statements)
references
References 46 publications
8
156
1
Order By: Relevance
“…Conversely, optogenetic activation of the VMHvl cells, either non-selectively or selectively in the Esr1 population induced attack towards castrated males, females and even inanimate objects [25, 67]. Electrophysiological recording showed that a quarter to a half of VMHvl cells respond maximally during attack and also carry information regarding the imminence and intensity of future attacks [25, 69, 70]. During interaction with a female, a subset of VMHvl cells are also activated (but to a much lesser extent) and the majority of the female-excited cells overlap with male excited cells [25, 69].…”
Section: The Hypothalamus Plays An Essential Role In Aggressive and Smentioning
confidence: 99%
“…Conversely, optogenetic activation of the VMHvl cells, either non-selectively or selectively in the Esr1 population induced attack towards castrated males, females and even inanimate objects [25, 67]. Electrophysiological recording showed that a quarter to a half of VMHvl cells respond maximally during attack and also carry information regarding the imminence and intensity of future attacks [25, 69, 70]. During interaction with a female, a subset of VMHvl cells are also activated (but to a much lesser extent) and the majority of the female-excited cells overlap with male excited cells [25, 69].…”
Section: The Hypothalamus Plays An Essential Role In Aggressive and Smentioning
confidence: 99%
“…In mice, a large number of distributed but interconnected brain areas have been implicated, including the prelimbic cortex (PL, part of the medial prefrontal cortex) and several of its projection targets (e.g. the amygdala, ventral tegmental area, NAc) (Okuyama et al 2016; Wong et al 2016; Lin et al 2011; Hitti & Siegelbaum 2014; Yizhar et al 2011; E. Lee et al 2016; van Kerkhof et al 2013; Takahashi et al 2014; Wang et al 2011; Bicks et al 2015; Gunaydin et al 2014; Felix-Ortiz et al 2016; Amadei et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Dotted gray lines represent known physical connections between the brain regions. The black line represents one functional connection that has been recently quantified in mice, the inhibitory projection from lateral septum (LS) to the ventrolateral portion of the ventromedial nucleus of the hypothalamus (VMHvl) (67). The pallium is shaded in blue, medial ganglion eminence (MGE) and anterior entopeduncular area (AEP) are shaded in yellow, lateral ganglionic eminence (LGE) is shaded in red, the preoptic area (POA) is shaded in orange, the hypothalamus is shaded in purple, and the midbrain is shaded in gray.…”
mentioning
confidence: 99%
“…Optogenetic stimulation of cells in the ventrolateral subdivision of the ventromedial nucleus of the hypothalamus (VMHvl) causes male mice to attack other males, females, and inanimate objects (53). Optogenetic activation of the LS and also, the LS-VMH projection suppresses fighting in male mice (67). However, on further probing of the functional relationship between LS and the VMHvl cells, it was found that 80% of VMHvl cells were inhibited by input from the LS but that some cells in the VMHvl showed an increase in their firing rate in response to LS optical stimulation, suggesting that there exist both attack-inhibited and -excited cells in the VMHvl (67).…”
mentioning
confidence: 99%
See 1 more Smart Citation